An Optical Frequency Comb Tied to GPS for Laser Frequency/Wavelength Calibration - Stone, Jack A. (J Res Natl Inst Stand Technol, 2010)
Optical frequency combs can be employed over a broad spectral range to calibrate laser frequency or vacuum wavelength. This article describes procedures and techniques utilized in the Precision Engineering Division of NIST (National Institute of Standards and Technology) for comb-based calibration of laser wavelength, including a discussion of ancillary measurements such as determining the mode order. The underlying purpose of these calibrations is to provide traceable standards in support of length measurement. The relative uncertainty needed to fulfill this goal is typically 10(−8) and never below 10(−12), very modest requirements compared to the capabilities of comb-based frequency metrology. In this accuracy range the Global Positioning System (GPS) serves as an excellent frequency reference that can provide the traceable underpinning of the measurement. This article describes techniques that can be used to completely characterize measurement errors in a GPS-based comb system and thus achieve full confidence in measurement results.